2016
DOI: 10.4314/tjpr.v15i5.18
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic-mass spectrometric analysis of ethanol extract of <i>Maesa perlaria</i> var <i>formosana</i>

Abstract: Purpose: This study analyzes the chemical composition of ethanol root extracts of Maesa perlaria var. formosana by gas chromatography-mass spectrometry (GC-MS

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…Babiwa and co-worker reported that 1,2,3-propanetriol, monoacetate containing in Citrullus lanatus and MPR seed exhibited antimicrobial activity against Pseudomonas aeruginosa, Escherichia coli, Bacillus subtilis, S. aureus, and C. albicans [49]. Furthermore, 2,4di-tert-butylphenol, the matched chemical substance detected in MGG, was reported that to possess DPPH free radical scavenging activity, total antioxidant capacity (Trolox equivalent antioxidant capacity), and reducing ability [50]. Furthermore, azetidine-derived carbamate was reported to inhibit monoacylglycerol lipase, a 33 kDa serine hydrolase [51].…”
Section: Phytochemical Analysis Using Gc-msmentioning
confidence: 99%
“…Babiwa and co-worker reported that 1,2,3-propanetriol, monoacetate containing in Citrullus lanatus and MPR seed exhibited antimicrobial activity against Pseudomonas aeruginosa, Escherichia coli, Bacillus subtilis, S. aureus, and C. albicans [49]. Furthermore, 2,4di-tert-butylphenol, the matched chemical substance detected in MGG, was reported that to possess DPPH free radical scavenging activity, total antioxidant capacity (Trolox equivalent antioxidant capacity), and reducing ability [50]. Furthermore, azetidine-derived carbamate was reported to inhibit monoacylglycerol lipase, a 33 kDa serine hydrolase [51].…”
Section: Phytochemical Analysis Using Gc-msmentioning
confidence: 99%
“…A number of these chemical components have established pharmacological potentials. Typically, 2,4-bis (1,1-dimethylethyl)-phenol found in both the subfractions is reported to possess anti-inflammatory (Amaral et al 2014;Chandrasekar et al 2015;Kumar, Bhatnagar & Srivastava 2011;Yogeswari et al 2012), neuronal and antioxidant (Yang et al 2016) effects. The 2,4-di-tert-butylphenol plays a significant role as an antioxidant and marine metabolite (NLM 2020).…”
Section: Discussionmentioning
confidence: 99%